Gambaran konsep diri siswa di sekolah menengah kejuruan sumbangsih Jakarta Selatan - Sisca Folastri; Wahyu Eka Prasetyaningtyas (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2017)
This research aims to gives an overview of the self-concept of students SMK Sumbangsih Jakarta Selatan based from four aspects (physical,condision, social relations, emotional state and intellectual ability). Schools are responsible for improving the quality of education and developing self-concept of students in a positive direction. This research uses survey method and data analysis by simple statistical analysis. The sample in this research is 45 students by using saturated sempling techniques. The result of this research shows that the self-concept of students SMK Sumbangsih Jakarta Selatan are in very high category. In conclusion, students of SMK Sumbangsih have very high and high self-concept based on physical,condision, social relations, emotional state and intellectual ability. The implications of research results for BK teachers are the basis for the preparation of BK service programs in order to develop and improve student self-concept in a positive direction.